1997
DOI: 10.1086/514514
|View full text |Cite
|
Sign up to set email alerts
|

Leclercia adecarboxylataInfections: Case Report and Review

Abstract: Leclercia adecarboxylata has been rarely isolated from environmental and clinical specimens. On review of the world literature, we found two reports of L. adecarboxylata infection: one report described a patient with hepatic cirrhosis, and the other described a child dependent on total parenteral nutrition. L. adecarboxylata was isolated from five infected patients who were evaluated at our institution. Three patients had lower-extremity wound infections in which L. adecarboxylata was part of a mixed microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 8 publications
0
73
0
Order By: Relevance
“…Conventional biochemical tests were used for the phenotypic identification of aerobic and anaerobic bacteria (22,24). For some nonfermenting aerobic bacteria, the MicroLog system, release 4.0 (Biolog, Inc., Hayward, Calif.), was used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional biochemical tests were used for the phenotypic identification of aerobic and anaerobic bacteria (22,24). For some nonfermenting aerobic bacteria, the MicroLog system, release 4.0 (Biolog, Inc., Hayward, Calif.), was used.…”
Section: Methodsmentioning
confidence: 99%
“…It has been estimated that there are 500,000 cases of bacteremia each year, with an associated crude mortality of 35% (28). The rapid and reliable detection and subsequent identification of microorganisms from blood remain critical so that the appropriate antimicrobial therapy can be provided.DNA sequencing of conserved regions within phylogenetically informative genetic targets, such as the small-subunit (16S) rRNA gene, is promising as a means for identifying bacteria (5,9,22,27). Broad-range PCR primers can be used to amplify highly conserved regions of the 16S rRNA gene from a wide range of organisms; highly variable regions within the amplicon permit phylogenetic analysis and, in many cases, species-level identification (7, 29).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Leclercia adecarboxylata is a part of normal flora in the gut of animals and its epidemiological significance is not clear though it has been recovered from cases of wound infection, bacteraemia, sputum samples, urinary tract infections, vaginal discharge. [6][7][8] Most recently it has been reported from India, as the cause of ventilator associated pneumonia and pharyngeal, peri-tonsillar abscess and in immune-competent patients. 9,10 It has most commonly been isolated from different infections as a part of mixed flora and most of the cases were immunecompromised, the clinical significance of which is not clear.…”
Section: Discusssionmentioning
confidence: 99%
“…9,10 It has most commonly been isolated from different infections as a part of mixed flora and most of the cases were immunecompromised, the clinical significance of which is not clear. 6,11 Few reports raised suspicion of association between L. adecarboxylata cutaneous infection and contaminated sea water especially in cases wound infection among healthy individuals. 12 Stock et al studied the natural antimicrobial susceptibility pattern of 101 strains and showed that all of them were naturally sensitive to all tested aminoglycosides.…”
Section: Discusssionmentioning
confidence: 99%